2022
DOI: 10.3390/ijms23136879
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Modulation: Potential Therapeutic Target for Glioblastoma Treatment

Abstract: Glioblastoma multiforme is a lethal disease and represents the most common and severe type of glioma. Drug resistance and the evasion of cell death are the main characteristics of its malignancy, leading to a high percentage of disease recurrence and the patients’ low survival rate. Exploiting the modulation of cell death mechanisms could be an important strategy to prevent tumor development and reverse the high mortality and morbidity rates in glioblastoma patients. Ferroptosis is a recently described type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 133 publications
(170 reference statements)
0
10
0
Order By: Relevance
“…Hence, the inductors of ferroptosis, the only unequivocally oxidative stress- and lipid peroxidation-driven cell death, may give a novel perspective on anti-cancer therapy. Not accidentally, the role of ferroptosis in cancer treatment is a matter of intensive research [ 25 ]. This is why our research group found it surprising that the connection between this lipid ROS-driven cell death and one of the major oxidative stress-triggered signaling pathways, the JNK pathway, has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the inductors of ferroptosis, the only unequivocally oxidative stress- and lipid peroxidation-driven cell death, may give a novel perspective on anti-cancer therapy. Not accidentally, the role of ferroptosis in cancer treatment is a matter of intensive research [ 25 ]. This is why our research group found it surprising that the connection between this lipid ROS-driven cell death and one of the major oxidative stress-triggered signaling pathways, the JNK pathway, has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a recently discovered intracellular iron-dependent form of cell death characterized by the overproduction of reactive oxygen species (ROS) and accumulation of lipid peroxidation, leading to cell death [ 116 ]. As glioblastoma cells have higher ROS and iron accumulation than healthy tissues, they are especially susceptible to death by ferroptosis [ 117 , 118 ]. As a result, ferroptosis induction inhibits glioblastoma tumor growth, improves patient survival and increases the efficacy of radio- and chemotherapy, thereby providing adjuvant antitumor options [ 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are natural products known for a plethora of bioactivities, including their diverse effects on ferroptosis cell death [ 13 , 14 , 15 , 16 , 17 , 49 ]. They have shown significant anticancer activity in vitro, even against an aggressive type of cancer, and their chemopreventive role has been summarized elsewhere [ 50 , 51 ].…”
Section: Biological Aspects Of Ferroptosis Modulatorsmentioning
confidence: 99%
“…Herein, we collect sets of 30 representative inducers ( Table 1 and Table S1 ) and 48 suppressors/inhibitors ( Table 2 and Table S2 ) of ferroptotic cell death with a MW of less than 800 and analyze them in relation to structural, physicochemical/drug-likeness, and biological/pharmacological aspects. Thereafter, the review focuses on describing the biological activities/effects of the subset of (poly)phenolic ferroptosis modulators since, to our knowledge, there has been no such comprehensive review of polyphenols as ferroptosis modulators [ 13 , 14 , 15 , 16 , 17 ]. We focus only on the activities of (poly)phenolic compounds (many of which are already known) in conjunction with their reported (anti)ferroptotic effects.…”
Section: Introductionmentioning
confidence: 99%